FORAMINIFEROS DEL CRETACICO INFERIOR EN LOS NIVELES BASALES DE LA FORMACION AGRIO, PERFIL EL MARUCHO, NEUQUEN, ARGENTINA. (Ameghiniana, 2014)
The present paper deals with a benthonic foraminiferal fauna, Uppermost Valanginian to Lower Hauterivian in Age. In this presumably euhaline shallowepineritical association thirteen species, mainly nodo~oarians, are recognized. Most of the species are included in geographically well-distributed taxa. Marginulinopsis picunleufuensis tenuistriata nov. subsp. is proposed